Endoscopic submucosal dissection for superficial esophageal squamous cell carcinoma in patients with cirrhosis and esophageal varices. Issue 1 (24th May 2022) - Mochimaru, Tomoaki; Hikichi, Takuto; Hashimoto, Minami; Nakamura, Jun; Takasumi, Mika; Kato, Tsunetaka; Kobashi, Ryoichiro; Yanagita, Takumi; Suzuki, Rei; Sugimoto, Mitsuru; Sato, Yuki; Irie, Hiroki; et al.
Abstract: Endoscopic submucosal dissection (ESD) has become the standard treatment for superficial esophageal squamous cell carcinoma (SESCC). However, the treatment strategy for SESCC complicated by esophageal varices (EVs) has not been established. We report two cases of SESCC in patients with alcoholic cirrhosis complicated by EVs who underwent ESD. Case 1 presented with EVs on the anal side of the SESCC, and endoscopic variceal ligation (EVL) was performed before ESD. After EVL, the SESCC was successfully treated by ESD without any adverse events. Case 2 presented EVs from the anal side of the SESCC to the submucosa just below the SESCC. Then, EVL and endoscopic injection sclerotherapy with polidocanol were performed before ESD. However, ESD was not completed because of severe bleeding by uncontrolled blood flow below and around the SESCC. Bleeding during ESD was controlled in case 1, but not in case 2.